Ventajas de uso de tocolíticos para la prolongación del embarazo - Reyes Rosero, Daysi Ivonne (2023)
ABSTRACT When analyzing the threat of premature birth, it described as the presence of contractions at a rate of 4 every 20 minutes or 8 in 60 minutes within the range of 28 and 36.6 weeks of gestation. The aim of the study was to determine the advantages of the use of tocolytics in the prolongation of pregnancy. The bibliographic review utilizes a type of descriptive, documentary and crosssectional research. We worked with 30 scientific evidence including systematic reviews and metaanalysis from 2017 up until this year. By systematizing the bibliographic information, it identified worldwide that nifedipine had a 90% prolongation of pregnancy. Studies consider that it is the preferred drug due to its efficacy and for its safety; it acts as a uterine inhibitor. Its period of prolongation of childbirth is 48 hours to 7 days. Followed by Atosiban since it has the same tolerance and safety to administer it, magnesium sulfate is not considered a medicine of choice because it has adverse effects such as nausea, tremors, vomiting, hypotension, tachycardia, headache. The first-choice tocolytic agent continues to be a topic of debate and varies considerably in all parts of the world; there are several types of tocolytic agents, of which, according to scientific evidence, the most used worldwide are Atosiban, nifedipine, magnesium sulfate and Indomethacin; in addition, at the national level, in Ecuador the most used are magnesium sulfate, It concluded that 90% of the drug of choice is nifedipine due to the longevity of pregnancy and the risk of less adverse effects, in addition the authors mention that the idea of combining nifedipine/Indomethacin as a form of therapy should not be ruled out since it has been proven to have greater efficacy unlike monotherapy. Magnesium sulfate would be a replacement for tocolytic if tocolytic agents of greater safety and tolerance for its multiple adverse effects are not available. Keywords: preterm labor, tocolytics, uteroinhibitors, prolongation of pregnancy. Reviewed by: Firmado electrónicamente por: MARITZA DE LOURDES CHAVEZ AGUAGALLO Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324